Umbrella-Review, Evaluation, Analysis and Communication Hub (U-REACH): a novel living umbrella review knowledge translation approach - Marco Solmi; David Moher; Samuele Cortese; Corentin J Gosling; Richard Delorme; Joaquim Radua (BMJ Mental Health)
Systematic reviews and meta-analyses have become crucial for evidence-based decision-making in recent decades. However, it is common for the results of multiple reviews on the same topic to be inconsistent, and it is widely recognised that the results of the reviews are not always effectively communicated to healthcare professionals and the lay public. This manuscript proposes a strategy to summarise and communicate the findings of previous systematic reviews and meta-analyses to wider audiences. The proposed approach couples the findings of umbrella reviews with the creation of open-access online platforms that present the results of these umbrella reviews in an accessible way to various stakeholders. The key potential methodological avenues of this approach are presented, and specific examples from the author’s own works and those from other teams are provided. An accompanying website (https://u-reach.org/) has been designed to present this Umbrella-Review, Evaluation, Analysis, and Communication Hub (U-REACH) approach and to overcome the technical challenges associated with this type of project (by sharing the code used to build existing U-REACH projects). The present document is intended to serve as a methodological and technical guide for the creation of large-scale projects designed to synthesise and disseminate scientific information to a broad audience.